Reconstructing 120 years of climate change impacts on Joshua tree flowering - Jeremy B. Yoder; Ana Karina Andrade; Lesley A. DeFalco; Todd C. Esque; Colin J. Carlson; Daniel F. Shryock; Ray Yeager; Christopher I. Smith (Ecology Letters, 2024)
Quantifying how global change impacts wild populations remains challenging, especially for species poorly represented by systematic datasets. Here, we infer climate change effects on masting by Joshua trees ( Yucca brevifolia and Y. jaegeriana ), keystone perennials of the Mojave Desert, from 15 years of crowdsourced observations. We annotated phenophase in 10,212 geo‐referenced images of Joshua trees on the iNaturalist crowdsourcing platform, and used them to train machine learning models predicting flowering from annual weather records. Hindcasting to 1900 with a trained model successfully recovers flowering events in independent historical records and reveals a slightly rising frequency of conditions supporting flowering since the early 20th Century. This reflects increased variation in annual precipitation, which drives masting events in wet years—but also increasing temperatures and drought stress, which may have net negative impacts on recruitment. Our findings reaffirm the value of crowdsourcing for understanding climate change impacts on biodiversity.

Sharing and reporting benefits from biodiversity research - Emily Marden; Richard J. Abbott; Frédéric Austerlitz; Daniel Ortiz‐Barrientos; Regina S. Baucom; Pim Bongaerts; Aurélie Bonin; Camille Bonneaud; Luke Browne; C. Alex Buerkle; Ana L. Caicedo; David W. Coltman; et al. (Molecular Ecology, 2021)

Asymmetric hybridization and gene flow between J oshua trees ( A gavaceae: Y ucca ) reflect differences in pollinator host specificity - Tyler N. Starr; Katherine E. Gadek; Jeremy B. Yoder; Ramona Flatz; Christopher I. Smith (Molecular Ecology, 2013)
The angiosperms are by far the largest group of terrestrial plants. Their spectacular diversity is often attributed to specialized pollination. Obligate pollination mutualisms where both a plant and its pollinator are dependent upon one another for reproduction are thought to be prone to rapid diversification through co‐evolution and pollinator isolation. However, few studies have evaluated the degree to which pollinators actually mediate reproductive isolation in these systems. Here, we examine evidence for hybridization and gene flow between two subspecies of Joshua tree ( Y ucca brevifolia brevifolia and Y ucca brevifolia jaegeriana ) pollinated by two sister species of yucca moth. Previous work indicated that the pollinators differ in host specificity, and DNA sequence data suggested asymmetric introgression between the tree subspecies. Through intensive sampling in a zone of sympatry, a large number of morphologically intermediate trees were identified. These included trees with floral characters typical of Y . b. jaegeriana , but vegetative features typical of Y . b. brevifolia . The opposite combination— Y . b. brevifolia flowers with Y . b. jaegeriana vegetative morphology — never occurred. Microsatellite genotyping revealed a high frequency of genetically admixed, hybrid trees. Coalescent‐based estimates of migration indicated significant gene flow between the subspecies and that the direction of gene flow matches differences in pollinator host fidelity. The data suggest that pollinator behaviour determines the magnitude and direction of gene flow between the two subspecies, but that specialized pollination alone is not sufficient to maintain species boundaries. Natural selection may be required to maintain phenotypic differences in the face of ongoing gene flow.

Host specificity and reproductive success of yucca moths ( Tegeticula spp. Lepidoptera: Prodoxidae) mirror patterns of gene flow between host plant varieties of the Joshua tree ( Yucca brevifolia : Agavaceae) - CHRISTOPHER IRWIN SMITH; CHRISTOPHER S. DRUMMOND; WILLIAM GODSOE; JEREMY B. YODER; OLLE PELLMYR (Molecular Ecology, 2009)
Coevolution between flowering plants and their pollinators is thought to have generated much of the diversity of life on Earth, but the population processes that may have produced these macroevolutionary patterns remain unclear. Mathematical models of coevolution in obligate pollination mutualisms suggest that phenotype matching between plants and their pollinators can generate reproductive isolation. Here, we test this hypothesis using a natural experiment that examines the role of natural selection on phenotype matching between yuccas and yucca moths (Tegeticula spp.) in mediating reproductive isolation between two varieties of Joshua tree (Yucca brevifolia var. brevifolia and Y. brevifolia var. jaegeriana) . Using passive monitoring techniques, DNA barcoding, microsatellite DNA genotyping, and sibship reconstruction, we track host specificity and the fitness consequences of host choice in a zone of sympatry. We show that the two moth species differ in their degree of host specificity and that oviposition on a foreign host plant results in the production of fewer offspring. This difference in host specificity between the two moth species mirrors patterns of chloroplast introgression from west to east between host varieties, suggesting that natural selection acting on pollinator phenotypes mediates gene flow and reproductive isolation between Joshua‐tree varieties.